MEMBANGUN RELASI SOSIAL MELALUI KOMUNIKASI EMPATIK (PERSPEKTIF PSIKOLOGI KOMUNIKASI) - Ade Masturi (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2010)
Empathy is one of the important elements in communication. It is the basic mode of communication,especially for adults. Empathic communication is effective when it is based on the awareness for understanding, care andattention between the communicator and communicant. The are some principles that should be applied, such as entire,morals, trying to understanding, belief, eye contact, smile, and understanding.